Inhibition of Cycloartenol Synthase (CAS) Function in Tobacco BY‐2 Cell Suspensions: A Proteomic Analysis. Issue 8 (30th June 2015) - Gas‐Pascual, Elisabet; Simonovik, Biljana; Heintz, Dimitri; Bergdoll, Marc; Schaller, Hubert; Bach, Thomas J.
Abstract: The effect of an inhibitor of cycloartenol synthase (CAS, EC 5.4.99.8) on the proteome of tobacco BY‐2 cells has been examined. CAS catalyzes the first committed step in phytosterol synthesis in plants. BY‐2 cells were treated with RO 48‐8071, a potent inhibitor of oxidosqualene cyclization. Proteins were separated by two‐dimensional electrophoresis and spots, that clearly looked differentially accumulated after visual inspection, were cut, in‐gel trypsin digested, and peptides were analyzed by nano‐HPLC–MS/MS. Distinct peptides were compared to sequences in the data banks and attributed to corresponding proteins and genes. Inhibition of CAS induced proteins that appear to mitigate the negative effects of the chemical exposure. However, as all enzymes that are directly involved in phytosterol biosynthesis are low‐abundant proteins, significant changes in their levels could not be observed. Differences could be seen with enzymes involved in primary metabolism (glycolysis, pentose phosphate pathway etc.), in proteins of the chaperonin family, and those, like actin, that participate in formation and strengthening of the cytoskeleton and have some impact on cell growth and division.